2016
DOI: 10.13040/ijpsr.0975-8232.7(9).3602-10
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Herbal immunomodulator is substance which stimulates or suppresses the components of immune system including both innate and adaptive immune responses. The modulation of immune system by various medicinal plant products has become subject for scientific investigations currently worldwide. A number of Indian medicinal plants and various "Rasayana" have been claimed to possess immunomodulatory activity. Some of these plants are, Allium sativum, Morus alba, Acacia catechu, Tinospora cordifolia, and Mangifera indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Here, scrocaffeside A is collected from the methanol extract of the plant to investigate its potential as an immunomodulator. An et al (2009) and later, Singh et al (2016) studied its effect on the BALB/c male mice model [ 249 ]. They found that Scrocaffeside A enhanced the proliferation of splenocytes and their response to polyclonal T cell mitogen concanavalin A (Con A) and lipopolysaccharide (LPS) in addition to increasing the production of cytokines and the CD4/CD8 population of splenocytes.…”
Section: Promising Natural Immunomodulators Not Yet Studied Against S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, scrocaffeside A is collected from the methanol extract of the plant to investigate its potential as an immunomodulator. An et al (2009) and later, Singh et al (2016) studied its effect on the BALB/c male mice model [ 249 ]. They found that Scrocaffeside A enhanced the proliferation of splenocytes and their response to polyclonal T cell mitogen concanavalin A (Con A) and lipopolysaccharide (LPS) in addition to increasing the production of cytokines and the CD4/CD8 population of splenocytes.…”
Section: Promising Natural Immunomodulators Not Yet Studied Against S...mentioning
confidence: 99%
“…A dose-dependent increase in the activity of macrophages and the natural killer cells was observed when treated with 5–125 μg/mL dose of scrocaffeside A and a similar pattern was seen in case of mature T-cell subsets. It was seen that there were increased levels of interleukin (IL)-2, IL-4, IL-12, and (IFN)-gamma expression within the male mice [ 249 , 250 ]. Hence, these effects of scrocaffeside A demonstrated its prospect for the immunostimulation properties which should be explored for the treatment of COVID-19 infection.…”
Section: Promising Natural Immunomodulators Not Yet Studied Against S...mentioning
confidence: 99%